2020
DOI: 10.1101/2020.01.03.893149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of DNAJ-HSP70 interaction improves strength in muscular dystrophy

Abstract: Introduction: 41Limb-girdle muscular dystrophies (LGMD) are a family of hereditary muscle diseases 42 that are inherited in an autosomal recessive or dominant manner [1]. Most recessively 43 inherited LGMDs are postulated to be caused by a loss-of-function mechanism, 44 because the protein is absent in patient muscle tissue and many mutations lead to 45 premature stops or frameshifts. However, the mechanisms of dominantly inherited 46LGMDs are less clear: they may be due to haploinsufficiency, a gain of ne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Another study on chaperone regulation found that the underlying mechanism of the inherited muscular dystrophy disease LGMD1D is due to increased affinity between HSP70 and a mutated variant of the JDP DNAJB6, thereby locking HSP70 to this complex, preventing it from completing its cellular tasks. By inhibiting the interaction between HSP70 and DNAJB6, HSP70 molecules were released, relieving disease models from symptoms of muscular dystrophy [ 166 ].…”
Section: Co-chaperones Decide the Fate Of Hsp70-bound Substratesmentioning
confidence: 99%
“…Another study on chaperone regulation found that the underlying mechanism of the inherited muscular dystrophy disease LGMD1D is due to increased affinity between HSP70 and a mutated variant of the JDP DNAJB6, thereby locking HSP70 to this complex, preventing it from completing its cellular tasks. By inhibiting the interaction between HSP70 and DNAJB6, HSP70 molecules were released, relieving disease models from symptoms of muscular dystrophy [ 166 ].…”
Section: Co-chaperones Decide the Fate Of Hsp70-bound Substratesmentioning
confidence: 99%
“…The variant site, phenylalanine at 90, is within the conserved G/F domain in DNAJB4. Similar to the DNAJB6-F93L mutant, the DNAJB4-F90L mutant enhanced the formation of TDP-43-positive nuclear stress granules when expressed in cells, and the abrogation of its association with HSP70 suppressed TDP-43 stress granule formation 22 . These results suggested that the F90L variant in DNAJB4 has a gain-of- toxicity with HSP70 on TDP-43.…”
Section: Discussionmentioning
confidence: 91%
“…Because LGMDD1-mutant DNAJB6b showed a toxic gain-of-function effect through the interaction with HSP70 in cellulo models 22 , we hypothesized that DNAJB4 mutant also have a similar toxic gain-of-function effect. To test this, we first analyzed the subcellular localization of wild-type and mutant DNAJB4 in HeLa cells and found that DNAJB4-F90L did not change its localization (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations